2020
DOI: 10.1111/ejss.13015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of drought and rewetting on N2O emissions from soil in temperate and Mediterranean climates

Abstract: The potential for soils to produce nitrous oxide (N 2 O) is impacted by past moisture conditions; however, the extent of this impact is not fully understood. We conducted the first review of this, using two literature searches and a metaanalysis. We found 36 studies out of a possible 735 that described experiments

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In a recent literature review and meta-analysis, Barrat et al (2020) found that WFPS was a significant explanatory variable for N 2 O emissions and this was affected by the prior moisture status of the soil. In our experiments, the soils were prepared in a standard manner, so only the final moisture status at the start of the incubation differed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review and meta-analysis, Barrat et al (2020) found that WFPS was a significant explanatory variable for N 2 O emissions and this was affected by the prior moisture status of the soil. In our experiments, the soils were prepared in a standard manner, so only the final moisture status at the start of the incubation differed.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the speed of the SWC decrease could be included in N 2 O ux models for the drought period. This interpretation is supported by Barrat et al58 review on drought and rewetting effects on soil N 2 O uxes indicating that the larger the WFPS change, the larger the N 2 O pulse with the the largest emissions occurred at 70% WFPS. In our Freeze-Thaw period, a positive correlation between the near-oor air temperature and N 2 O ux was observed(Fig.…”
mentioning
confidence: 59%
“…Soil water content was the main factor associated with hot moments of N 2 O emission from soils, and it has been argued that drought and rewetting trigger such events by different mechanisms 58 . Likewise, we propose that hot moments in current study were caused by a variety of different mechanisms.…”
Section: Relationships Of N 2 O Ux and Environmental Parametersmentioning
confidence: 99%
“…In contrast, HMs are regulated by abiotic or biotic controls that are transient at a given location to elevate nutrient pools, processing rates, or uxes. For example, pulses of nutrients or microbial activity may only be activated immediately following re-wetting events of dry soil (McClain et al 2003;Harms and Grimm 2008;Barcellos et al 2018;Barrat et al 2021), or immediately after catastrophic disturbances such as wild re (Zhao et al 2021). In addition, dead and decaying roots or macrofauna can create biopores that accrue nutrients and serve as HMs of microbial activity (Kuzyakov and Blagodatskaya 2015;Hoang et al 2016).…”
Section: Introductionmentioning
confidence: 99%